Molecular Factors of Hypochlorite Tolerance in the Hypersaline Archaeon Haloferax volcanii - Gomez M.; Leung W.; Dantuluri S.; Pillai A.; Gani Z.; Hwang S.; McMillan L.J.; Kiljunen S.; Savilahti H.; Maupin-Furlow J.A. (MDPI, 2022)
Halophilic archaea thrive in hypersaline conditions associated with desiccation, ultraviolet (UV) irradiation and redox active compounds, and thus are naturally tolerant to a variety of stresses. Here, we identified mutations that promote enhanced tolerance of halophilic archaea to redox-active compounds using Haloferax volcanii as a model organism. The strains were isolated from a library of random transposon mutants for growth on high doses of sodium hypochlorite (NaOCl), an agent that forms hypochlorous acid (HOCl) and other redox acid compounds common to aqueous environments of high concentrations of chloride. The transposon insertion site in each of twenty isolated clones was mapped using the following: (i) inverse nested two-step PCR (INT-PCR) and (ii) semi-random two-step PCR (ST-PCR). Genes that were found to be disrupted in hypertolerant strains were associated with lysine deacetylation, proteasomes, transporters, polyamine biosynthesis, electron transfer, and other cellular processes. Further analysis revealed a Delta psmA1 (alpha 1) markerless deletion strain that produces only the alpha 2 and beta proteins of 20S proteasomes was hypertolerant to hypochlorite stress compared with wild type, which produces alpha 1, alpha 2, and beta proteins. The results of this study provide new insights into archaeal tolerance of redox active compounds such as hypochlorite.